Myopathy of distal lower limbs: the clinical variant of Miyoshi - Soares Cristiane N.; Freitas Marcos R.G. de; Nascimento Osvaldo J.M.; Silva Lenilda Ferreira da; Freitas Andréa R. de; Werneck Lineu C. (Arquivos de Neuro-Psiquiatria)
Miyoshi distal dystrophy is a rare myopathy characterized by an autosomal recessive pattern of inheritance and it is prevalent in Japan. Onset of disease is in early adult life with weakness and atrophy of the leg muscles. Recently gene linkage to chromosome 2p12-14 has been established. We report three sisters, born of consanguineous parents. All of them noticed weakness and atrophy of leg muscles, and could not walk on their heels. In all of them the creatine kinase concentrations were very high. The electromyography showed myopathic patterns and the muscle biopsy disclosed dystrophic changes and an absence of dysferlin. There are few cases reported of Miyoshi distal dystrophy in Latin America. The Miyoshi myopathy may be distinct among the hereditary distal myopathies.